VARIABEL MAKROEKONOMI TERHADAP INDEKS SAHAM SYARIAH INDONESIA (PERIODE MEI 2011-SEPTEMBER 2015 DENGAN MODEL ECM) - Yudhistira Ardana (Trunojoyo University of Madura, 2016)
This study aimed to analyze the effect of macroeconomic variables on Indonesian Islamic stock index. Macroeconomic variables used is the interest rate of Bank Indonesia (BI-rate), inflation, exchange rate, Bank Indonesia Certificates Sharia (SBIS) and world oil prices. The data used in this research is secondary data during the period May 2011 until September 2015 using a model error correction model (ECM) where the end result is going to measure the effect of macroeconomic variables on Indonesian Sharia Stock Index in the short term and long term.